Pedagogical Innovation Through Use of Electronic Portfolios in Higher Education - Ximena Elizabeth Naranjo Lozada; Silvia Elizabeth Cárdenas Sánchez; Jessica Valentina Galimberti (ESPOCH Congresses, 2021)
Abstract The use of electronic folders implies processes and dedication of both the student and the teacher to be able to develop the final product that demonstrates the development and growth of the student in the subject and promotes both formative and summative evaluation. Through the following study, it is proposed to know if students consider the use of appropriate electronic portfolios in English in higher education. In addition, it is important to understand the implications of the development of electronic portfolios based on the experiences obtained during the semester in which the strategy was implied. This qualitative study was carried out at the Escuela Superior Politécnica de Chimborazo Morona Santiago headquarters during the special academic period April - August 2020. It is important to mention that the use of the Pathbrite application was chosen to prepare the portfolio since you can add videos, text, images and other addresses or web pages to make up the portfolio. Thanks to the survey, it was also possible to know how it influenced personal growth and the improvement of the students' English level.